2020
DOI: 10.1021/acssuschemeng.0c02433
|View full text |Cite
|
Sign up to set email alerts
|

Ni–Cu Bimetallic Catalytic System for Producing 5-Hydroxymethylfurfural-Derived Value-Added Biofuels

Abstract: Biomass is the only renewable carbon source capable of replacing conventional production of chemicals and fuels derived from nonrenewable resources. The cellulose monomers derived from lignocellulosic biomass can be transformed into 5-hydroxymethylfurfural (HMF), which can be further converted into 2,5-dimethylfuran (DMF) and 2,5-dimethyltetrahydrofuran (DMTHF). These products can be used as substitutes for standard gasoline or as additives. This study has shown that by using Ni–Cu catalysts supported on ZrO2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…TEM and HRTEM images ( Figures 1C,D ) indicated that carbon balls were covered by carbon nanotubes, and Cu–Co metal particles were confined to the tips of the nanotubes with an average size of 6–8 nm. Figure 1D shows a lattice fringe of 0.209 nm attributable to the plane of Cu (111) ( Liu J et al, 2020 ; Viar et al, 2020 ), and a lattice distance of 0.203 nm attributable to the plane of metallic Co (111) ( Ma et al, 2020 ). In addition, the SEM and elemental images of Cu, Co, C in the 2CuCo–IG catalyst showed that copper and cobalt were uniformly dispersed throughout the catalyst ( Figures 1E–H ).…”
Section: Resultsmentioning
confidence: 99%
“…TEM and HRTEM images ( Figures 1C,D ) indicated that carbon balls were covered by carbon nanotubes, and Cu–Co metal particles were confined to the tips of the nanotubes with an average size of 6–8 nm. Figure 1D shows a lattice fringe of 0.209 nm attributable to the plane of Cu (111) ( Liu J et al, 2020 ; Viar et al, 2020 ), and a lattice distance of 0.203 nm attributable to the plane of metallic Co (111) ( Ma et al, 2020 ). In addition, the SEM and elemental images of Cu, Co, C in the 2CuCo–IG catalyst showed that copper and cobalt were uniformly dispersed throughout the catalyst ( Figures 1E–H ).…”
Section: Resultsmentioning
confidence: 99%
“…[36,37] Hydrogenation of biomass-derived HMF has been extensively studied and can give a variety of products, whose distribution depends on the catalyst used, its structure, and composition. [36,38,39] It consists of C=O, CÀ O, C=C, OH, and a furan ring group which can be hydrogenated to give various products via a flexible route. [22] Scheme 1 gives the various hydrogenated products that can be obtained from HMF.…”
Section: Hydrogenation Of Bio-based Carbonyl Compoundsmentioning
confidence: 99%
“…[22] Scheme 1 gives the various hydrogenated products that can be obtained from HMF. [36] The vapour phase selective hydrogenation of HMF to DMF and DMTHF using NiÀ Cu bimetallic system was carried out in a continuous fixed-bed reactor at 275 °C and 15 bar H 2 pressure for 25 h. [39] The catalysts were impregnated on zirconia, via wetness impregnation method using two approaches, namely, one-step impregnation/co-impregnation and two-step impregnation. The one-step impregnated catalyst was represented as YNiXCuZr where Y and X are the nominal weights of Ni and Cu, respectively.…”
Section: Hydrogenation Of Bio-based Carbonyl Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, DMF can be converted to p-xylene by the Diels-Alder reaction with ethylene. [13][14][15][16][17][18] The transformation of HMF into DMF usually involves multiple reaction steps (Scheme 1). In this respect, achieving selective hydrogenolysis of HMF has received much attention.…”
Section: Introductionmentioning
confidence: 99%